Bio stimulation of Nodules formation and growth of common bean by using Fenugreek Aqueous Seed Extract - S. Hussain, Wasan; Magdy Abbas, Mahmoud; H. Ali, Alaa; Nashowan, Rehan (Brazilian Journal of Biometrics, 2023)
To reduce the number of chemical compounds a big worldwide effort introducing modern biological methods in crop production. allelopathy is One of the possible solutions that involve both inhibitory and stimulatory biochemical interactions between plants. So, this work aimed to study the effect of aqueous seed extract of fenugreek on growth characters in terms of shoot height (cm), root length, number of leaves/plant as well as plant shoot and root dry weight (g) Photosynthetic pigments. All aqueous seed extract of fenugreek (2, 4, and 6%) showed a significant positive effect on growth parameters, and photosynthetic pigments The results showed that all treatments led to significant increases in Chlorophyll b and total for two bean cultivars (Iraqi 7 and Turkish) when compared to the corresponding controls. maximum significant increases of Chlorophyll b and total of both cultivars by treatment with 6% aqueous seed extract fenugreek, NPK ratio of both bean cultivars. The results revealed that 6% aqueous seed extract of fenugreek caused the maximum significant increases in the most of investigated parameters. Showed Formation of root nodules of bean cultivars (Turkish) by the effect of Concentration at 6% from Fenugreek Aqueous seed extract.